2021
DOI: 10.1186/s12883-021-02303-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness comparisons of drug therapies for postoperative aneurysmal subarachnoid hemorrhage patients: network meta‑analysis and systematic review

Abstract: Objective To compare the effectiveness of various drug interventions in improving the clinical outcome of postoperative patients after aneurysmal subarachnoid hemorrhage (aSAH) and assist in determining the drugs of definite curative effect in improving clinical prognosis. Methods Eligible Randomized Controlled Trials (RCTs) were searched in databases of PubMed, EMBASE, and Cochrane Library (inception to Sep 2020). Glasgow Outcome Scale (GOS) score… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Although many studies have reported that nimodipine and cilostazol can reduce DCI in patients with SAH, there are few reports on whether the combined treatment of both drugs has a better effect in preventing DCI [11,35]. Our data showed that the use of cilostazol combined with nimodipine decreases the incidence of DCI and ACV compared to nimodipine alone.…”
Section: Performance Evaluation Using ML Modelingsupporting
confidence: 46%
See 1 more Smart Citation
“…Although many studies have reported that nimodipine and cilostazol can reduce DCI in patients with SAH, there are few reports on whether the combined treatment of both drugs has a better effect in preventing DCI [11,35]. Our data showed that the use of cilostazol combined with nimodipine decreases the incidence of DCI and ACV compared to nimodipine alone.…”
Section: Performance Evaluation Using ML Modelingsupporting
confidence: 46%
“…Cilostazol is another option drug studied to prevent ACV [35]. Experimental and small clinical studies have shown good prognostic results in reducing ACV and DCI [36][37][38].…”
Section: Performance Evaluation Using ML Modelingmentioning
confidence: 99%
“…Specifically, hemodynamic characteristics, i.e., flow patterns, wall shear stress ( ), oscillatory shear index ( ), and time-averaged pressure ( TAP ), play an important role in the formation, growth, and rupture of cerebral aneurysms, and should be identified precisely using qualitative and quantitative manners [ 13 , 14 , 15 , 16 , 17 ]. So far, the risks associated with various factors (i.e., aneurysmal dome locations, high-risk aneurysmal morphologies, pre- and post-treatment states, and arterial blood flow conditions) on the pathophysiology of CAs have been estimated, to some extent, using different research strategies (i.e., in vivo, in vitro, and in silico), which were summarized by previous efforts [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Nevertheless, the pulsatile flow rates are typically patient-specific [ 26 , 27 ], and many studies had tentative investigations on how the varying pulsatile blood flow rates/pressures will influence hemodynamic characteristics (i.e., and ) in cerebral arteries or CAs [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] The studies have different conclusions about the best agents to use after SAH. For instance, Yu et al [ 39 ] concluded that nimodipine and cilostazol are effective, while Dayyani et al [ 40 ] suggested that nimodipine, nimodipine with magnesium, and high-dose clazosentan could potentially prevent morbidity and mortality. Lastly, Mishra et al [ 41 ] found that nicardipine prolonged-release implants and cilostazol could improve outcomes after SAH.…”
Section: Discussionmentioning
confidence: 99%